Civitas Eraviscorum und Aquincum - Piso, Ioan (Acta Classica Universitatis Scientiarum Debreceniensis, 2026)
The author presents his position in the highly complex debate on the relationship between the civitas Eraviscorum and the Roman city of Aquincum. He believes that Mount Gellért is the direct predecessor of the Roman settlement of Aquincum and that, therefore, it bore the same name. He then agrees with those who believe that, with the establishment of the municipium of Aquincum, the civitas Eraviscorum ceased to exist as a legal entity and was preserved in inscriptions only as a symbol. The latter aspect could perhaps be explained by the personal relationship between the future emperor Hadrian and this civitas when, in 106/108, he was governor of Lower Pannonia and later, in 118, when, as emperor, he was personally active on the Middle Danube.